A Continuous Gradient Colloidal Glass - Schöttle, Marius; Lauster, Tobias; Römling, Lukas; Vogel, Nicolas; Retsch, Markus (Advanced Materials, 2022)
Colloidal crystals and glasses manipulate light propagation depending on their chemical composition, particle morphology, and mesoscopic structure. This light-matter interaction has been intensely investigated, but a knowledge gap remains for mesostructures comprising a continuous property gradient of the constituting particles. Here, a general synthetic approach to bottom-up fabrication of continuous size gradient colloidal ensembles is introduced. Firstly, the technique synthesizes a dispersion with a specifically designed gradual particle size distribution. Secondly, self-assembly of this dispersion yields a photonic colloidal glass with a continuous size gradient from top to bottom. Local and bulk characterization methods are used to highlight the significant potential of this mesostructure, resulting in vivid structural colors along, and superior light scattering across the gradient. The process describes a general pathway to mesoscopic gradients. It can expectedly be transferred to a variety of other particle-based systems where continuous gradients will provide novel physical insights and functionalities.
Keywords: colloidal self-assembly; gradient size distribution; light scattering; mesoscale gradient